2013
DOI: 10.1152/japplphysiol.01127.2012
|View full text |Cite
|
Sign up to set email alerts
|

Prior caloric restriction increases survival of prepubertal obese- and PCOS-prone rats exposed to a challenge of time-limited feeding and physical activity

Abstract: Diane A, Vine DF, Heth CD, Russell JC, Proctor SD, Pierce WD. Prior caloric restriction increases survival of prepubertal obese-and PCOS-prone rats exposed to a challenge of time-limited feeding and physical activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…In the PCOS-prone model, we have shown that energy restriction and voluntary exercise intervention (4 h/day) at an early life stage can significantly attenuate reproductive and cardiometabolic aberrations ( 111 ). The combination of diet and exercise was shown to lower total body weight gain and body fat mass by 30% in PCOS-prone animals.…”
Section: The Female Jcr:la-cp Rat As a Model Of Pomentioning
confidence: 99%
“…In the PCOS-prone model, we have shown that energy restriction and voluntary exercise intervention (4 h/day) at an early life stage can significantly attenuate reproductive and cardiometabolic aberrations ( 111 ). The combination of diet and exercise was shown to lower total body weight gain and body fat mass by 30% in PCOS-prone animals.…”
Section: The Female Jcr:la-cp Rat As a Model Of Pomentioning
confidence: 99%